Tindak Pidana Kekerasan Seksual dan Perlindungan Hukum bagi Korban Kekerasan Seksual di Indonesia - Yusuf Saefudin; Fatin Rohmah Nur Wahidah; Rahtami Susanti; Luthfi Kalbu Adi; Prima Maharani Putri (Kosmik Hukum, 2023)
This study aims to describe the various forms of acts that fall into the category of criminal acts of sexual violence. In addition, this research is directed to comprehensively examine what forms of legal protection for victims of sexual violence in Indonesia have been specifically regulated in Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence. Therefore, this research is designed using the normative juridical method. Where the main data comes from laws and regulations, legal concepts related to sexual violence. The approaches used are statute approach and conceptual approach. The results showed, first, there are twelve types of sexual violence criminal offenses regulated in the TPKS Law. Second, Victims are entitled to Handling, Protection, and Recovery since the occurrence of Sexual Violence Crimes. Meanwhile, victims with disabilities are entitled to accessibility and reasonable accommodation for the fulfillment of their rights in accordance with the provisions of laws and regulations.Keywords: Legal Protection, Sexual Violence, Victims of Sexual Violence.